2005
DOI: 10.2105/ajph.2004.056523
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Dental Care and Unmet Dental Needs Among Low-Income Children

Abstract: Additional progress toward improving the dental health of low-income children depends on identifying and responding to factors limiting both the demand for and the supply of dental services. In particular, it appears that expanding access to dental benefits is key to improving the oral health of this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
52
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 8 publications
8
52
0
Order By: Relevance
“…Third, dental insurance coverage was parentally reported; parents may be unclear or inaccurate in their understanding of dental coverage. However, our estimate of uninsured children (22%) is somewhat close to the levels found in the 2002 the National Survey of America's Families (26%) 9 and in the 2001 California Health Interview Survey (23.6%). 18 Finally, the unmet need measure is subject to recognition and recall error, because it assumes that parents all recognize dental need and can recall this need at the interview time.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Third, dental insurance coverage was parentally reported; parents may be unclear or inaccurate in their understanding of dental coverage. However, our estimate of uninsured children (22%) is somewhat close to the levels found in the 2002 the National Survey of America's Families (26%) 9 and in the 2001 California Health Interview Survey (23.6%). 18 Finally, the unmet need measure is subject to recognition and recall error, because it assumes that parents all recognize dental need and can recall this need at the interview time.…”
Section: Discussionsupporting
confidence: 82%
“…4,6 Failure to obtain preventive dental care was more common among the children who came from low-income families, who were uninsured and non-Hispanic white, and who had a parent with less than a college education. 9,10 Yet, Oral Health in America: A Report of the Surgeon General 1 specifically calls for more data on dental care among diverse segments of the US population to eliminate health disparities, including racial and ethnic minorities, rural population, individuals with disabilities, immigrants, migrant workers, and the very young.…”
mentioning
confidence: 99%
“…The results of the PNAD 1998 showed that 18.7% of the Brazilian people had never consulted a dentist, and that this proportion was eight times higher for the lower-income group (39% versus 5%). Larger socioeconomic differentials were found among very young and old subjects 2,9 . Subsequent information (PNAD 2003: 15.9%; PNAD 2008: 11.7%) recorded a declining trend for this group.…”
Section: Introductionmentioning
confidence: 90%
“…Oral diseases mostly affect disadvantaged people 1 , who are less likely to receive dental care and more likely to have unmet needs than those in better social conditions 2,3,4 . Inequalities in access to dental services have been identified in several countries, regardless of the nature, scope and efficiency of their health systems 3,5,6,7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…This often causes them to forgo routine or preventive dental services and to seek access to dental services only after an acute dental problem arises. [3][4][5][6][7][8][9] Because few such people have an established relationship with a dentist, they frequently seek treatment for acute dental problems in an ED, where the non-lifethreatening nature of their dental problem places them at a low priority. They encounter long wait times, often experiencing acute pain, and once they are seen by a physician, they receive only limited treatment, such as nonnarcotic pain control, antibiotics, and a referral to a dentist.…”
Section: Lack Of Access To Dental Carementioning
confidence: 99%